Influence of Cavity Under Hydraulic Structures on Seepage Characteristics - Abdul Jabbar Jamel, Asmaa; Ibrahim Ali, Muataz (International Journal of Engineering and Technology, 2018)
Cavities under hydraulic structures have a significant influence on the stability of these structures. This study depends on (SEEP/W) software for a hydraulic structure model with an upstream sheet pile. Thus, different results are obtaining for discharge, uplift pressure and exit gradient. For the output a dimensional analysis is perform to study the effect of these variables. Also (SPSS), where special equations are obtaining for seepage discharge, uplift pressure and exit gradient has a coefficient of determination and correlation (0.9, 0.89, 0.8) respectively. The effect of the presence of the cavities on seepage properties whenever the location of the cavity before the sheet pile increased its effect on the discharge and uplift pressure in contrast to the exit gradient where cavity approaching the end of the structure that is increasing its impact on the exit gradient. Also decrease the depth of the cavity from ground increase its impact on the characteristics of seepage, as well as the greater coefficient of permeability and the diameter of the cavitation will increase seepage properties. Also shows that when comparing the state of the presence of cavity with the absence of it, different behaviors with different characteristics of seepage will appear at different percentage.